Design of Compressor less Solar Powered Refrigerator - Mehdi, Saghar (International Journal of Scientific Research and Management (IJSRM), 2016)
The thermoelectric effect has been proven as a source of cooling and small power generation as defined by the Peltier-Seebeck effect. Thermoelectric modules, optimized by semiconductors, have been used for temperature regulation by operating as a heat pump to maintain computing devices and integrated circuits at optimum temperatures for improved processing efficiency. Thermoelectric modules have also been used to capture microwatt electrical power from personal computing and other small scale devices by way of utilizing the waste heat rejected through its heat sink. In modern data centers and server farms, water cooling of electronics has been widely adapted as a more efficient cooling method than standard air conditioning and ventilation systems due to its vastly larger thermal capacity. However, even high density electronics cabinets and processing units are low level heat applications unfit for waste heat recovery by standard thermodynamics cycles and heat pumps. When applying the thermoelectric effect to the temperature difference between the heat source of the processing electronics and the heat sink of a water cooling system, potential exists for practical and economic energy recovery.This study demonstrates the feasibility of waste energy recovery from high power density electronics in data centers and server farms by way of the practical and economic application of thermoelectricity. An overview of thermoelectricity and the thermoelectric effect is given, including a review of semiconductor materials and electronics cabinet cooling techniques. This report describes an investigation into the efficiency of applying thermoelectricity to low temperature waste heat situations. Conclusions are presented concerning the effectiveness of this application towards waste heat utilization for power recovery.